2003
DOI: 10.1073/pnas.0630530100
|View full text |Cite
|
Sign up to set email alerts
|

Rapid evolution of the neutralizing antibody response to HIV type 1 infection

Abstract: A recombinant virus assay was used to characterize in detail neutralizing antibody responses directed at circulating autologous HIV in plasma. Examining serial plasma specimens in a matrix format, most patients with primary HIV infection rapidly generated significant neutralizing antibody responses to early (0 -39 months) autologous viruses, whereas responses to laboratory and heterologous primary strains were often lower and delayed. Plasma virus continually and rapidly evolved to escape neutralization, indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

55
1,101
4
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,083 publications
(1,166 citation statements)
references
References 36 publications
55
1,101
4
6
Order By: Relevance
“…High fidelity functional Env clones of the TF virus and later variants obtained by single genome amplification (SGA) have been used to demonstrate multiple rounds of autologous neutralization and escape over the course of infection (67). In most cases contemporaneous serum at each stage of escape is capable of neutralizing earlier but not later autologous Env variants (67, 84). Finally, as mentioned above, it is noteworthy that the UCA of most bnAb lineages exhibited little or no neutralizing activity against the autologous Tier 2 T/F virus.…”
Section: Neutralization Assessment Of Bnab Lineage Developmentmentioning
confidence: 99%
“…High fidelity functional Env clones of the TF virus and later variants obtained by single genome amplification (SGA) have been used to demonstrate multiple rounds of autologous neutralization and escape over the course of infection (67). In most cases contemporaneous serum at each stage of escape is capable of neutralizing earlier but not later autologous Env variants (67, 84). Finally, as mentioned above, it is noteworthy that the UCA of most bnAb lineages exhibited little or no neutralizing activity against the autologous Tier 2 T/F virus.…”
Section: Neutralization Assessment Of Bnab Lineage Developmentmentioning
confidence: 99%
“…The development of antibody responses follows a pattern, with antiviral antibodies being detected first as immune complexes41 followed by free antibody directed at the HIV‐1 envelope (Env) glycoprotein 41 (gp41) subunit,41, 42 and then by the development of Env glycoprotein 120 (gp120)‐binding antibodies 41. These early antibody responses do not neutralize or place selective pressure on virus evolution41; antibodies capable of neutralizing autologous viruses are not detectable until weeks to months after infection is established19, 20 and have little to no activity against heterologous HIV‐1 strains 43. The initial gp41‐directed antibody response is polyreactive and the antibodies are highly mutated,42 and evidence indicates that at least some early responding B cells are primed prior to infection by non‐HIV‐1 antigens such as proteins contained in intestinal microbiota 44…”
Section: Development Of Broadly Neutralizing Antibodies In Hiv‐1 Infementioning
confidence: 99%
“…Neutralization has been shown to exert immune pressure on HIV‐1,19, 20 while the role of other antibody‐mediated functions in exerting immune pressure is unclear, primarily because antibodies that mediate ADCC and other activities often also neutralize 21. Regardless, multiple studies have demonstrated that virus neutralization is a driver of both virus and antibody diversity,22, 23, 24, 25, 26 although neutralization of autologous viruses does not always cause the extinction of susceptible virus populations in an infected individual 25…”
Section: Introductionmentioning
confidence: 99%
“…These NAbs inhibit viral entry by blocking virion attachment to its receptors or membrane fusion [1]. During natural infection the effect of the autologous neutralization response appears to be limited, since the virus rapidly escapes the immune pressure in most individuals [2][3][4][5][6]. Therefore, eliciting robust neutralizing antibody responses against diverse HIV strains remains a major obstacle for vaccine development.…”
Section: Introductionmentioning
confidence: 99%